PENGARUH STRESS KERJA DAN KEPEMIMPINAN TERHADAP KINERJA KARYAWAN PT. BANK SUMUT CABANG SUKARAMAI MEDAN - Butar-Butar, Radot Rinaldi; Yunita, Nindya (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2025)
This research aims to determine the effect of occupational Stress and leadership on employee performance at PT Bank Sumut Sukaramai Medan Branch. The type of data in this study is associative. The population in this study was all employees of PT Bank Sumut branch Sukaramai Medan as much as 35 people. Data retrieval technique in the form of dissemination questionnaire to office employees at PT Bank Sumut branch Sukaramai Medan. Data analysis using the validity and reliability test, classic assumption test, hypothesis test, statistical test using multiple linear analysis models using multiple linear analysis models and determination tests T test results can be seen that T count on a working stress variable of-1,752 is greater than t table of 1,689 with a probability of t that is sig 0089. Based on these values then the working stress variable has no positive and insignificant effect on the performance variable and the value of the leadership count of 6,649 is greater than t table of 1,689 with sig level 0.000 is smaller than the limit Significance of 0.005, then the leadership variables partially have a positive and significant influence on the performance variables. Based on the F test result, the Fcalculate value of 25,784 is greater than the Ftabel of 3.17, meaning that working stress and leadership simultaneously positively and significantly affect the performance variables. The value of Asjusted R Square obtained is 0.593. The figure shows that 59.3% of performance (bound variables) can be explained by work stress and leadership. The remaining 30.7% is influenced by other factors not described in this study.